Saying Yes to Freestyle Volunteering: Doubting and Believing - Judy Lightfoot (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
My formerly academic interest in Peter Elbow's work developed fresh relevance a few years ago after a member of my family was diagnosed with schizophrenia. To volunteer "outside the box" with individuals who suffer from mental illness or homelessness, I needed a skeptic's doubt as well as an enthusiast :S belief But the first step was believing.